The Effect of Thriller Movie Content on Anxiety Levels and Interpersonal Relationship Patterns of Gen Z Students - Sandrila, Widya; Noviyanti, Pitri; Zahrah, Erlita; Ridho, Kholis (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
This study examines the influence of thriller movies on anxiety and interpersonal relationship patterns of Gen Z students in Indonesia. The method used was quantitative with a survey approach, involving 123 respondents. Data was obtained through a questionnaire containing 12 multiple choice questions and 3 essay questions, using a Likert scale to measure respondents' attitudes and opinions. The results showed that most respondents felt anxiety when watching intense scenes in thriller movies and thought of bad scenarios more often. However, the impact on sleep difficulties and unreasonable anxiety was not significant. In addition, thriller movies affected the pattern of interpersonal relationships with respondents becoming more cautious in trusting others and more empathic to other people's emotional situations. Based on the Uses and Gratification theory, thriller movies are chosen to fulfill emotional and entertainment needs. The findings reveal how media, particularly thriller movies, can affect young people's psychological well-being and social relationships.